(untitled) (Castilla. Estudios de Literatura, 2022)
The discovery of a new document linking Jerónimo de Pasamonte with the Monasterio de Piedra is reported. This document is related to those that were already known, and it is briefly explained that it was in the Monasterio de Piedra where Jerónimo de Pasamonte was able to compose the apocryphal Quixote.